Kepribadian Guru Dalam Novel “Guru Aini” Dan Relevansinya Terhadap Kompetensi Kepribadian Guru - Muhamad Iqbal; Mikyal Hardiyati (Tematik: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to identify the teacher character's personality in the novel and examine its relevance to the standards of teacher personality competencies as stated in Permendiknas No. 16 of 2007. The research employs a qualitative approach, grounded in a literature study, utilizing content analysis techniques to examine narratives that portray the character of the teacher in the novel. The results of the study show that the teacher character in the novel Guru Aini has a steady, mature, wise, and authoritative personality, and is an example, which directly reflects the dimensions of the teacher's personality competence. This research emphasizes that literary works can be a reflective medium in forming an understanding of professional teacher figures and the importance of personality development in the world of education.